A Review: Tailor-made Hydrogel Structures (Classifications and Synthesis Parameters). (2nd January 2016) - Singhal, Reena; Gupta, Kshitij
ABSTRACT: Hydrogels are being prepared for use in a wide variety of applications ranging from medicines, tissue engineering, superabsorbents, controlled release of drugs & fertilizers, and oil absorbers etc. This review highlights hydrogel structure and their different classifications under various heads. It also discusses various routes to obtain tailormade hydrogels by polymerizing a combination of two or more monomers with proper type of crosslinks in order to obtain desired properties in the resulting hydrogel. Novel hydrogel configurations like microgels and nanogels, slide ring gels, double network hydrogels and nanocomposite gels have also been reviewed. GRAPHICAL ABSTRACT: